Finest Hour (Reﬂections of an OR Nurse) - Donald, Joan (Operating Room Nurses Association of Canada Journal, 2000)
While spending a number of hours in an airport as I awaited my ﬂight, I walked by an advertisement which read “When Will Your FINEST HOUR Be?” Each time I passed the ad I became increasingly fascinated by it and I started wondering - at the end of the day, what would I say was my FINEST HOUR? I thought of so many events that have been significant and that brought joy into my life. I remember graduating from high school, from nursing school, and university. I thought about the day I was married and the delight of having two wonderful children. How rewarding it was when I was recognized by my peers and received an award or when I did a presentation that was well received by my audience. I mulled all these events over in my mind and wondered how could I ever pick one and say it was tops?